Kajian Tafsir Tematik tentang Pelestarian Lingkungan Hidup - Mardiana, Mardiana (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2017)
Official concept behind the term environment in the aspects of both teaching and scientific tradition of Islam does not have a concrete outlining such as the concept of neighborhood, which has been fitted in the framework of definition and scientific terminology. The conceptualization of environment in Islam implies rational comprehension of the kauniyah verses presented before men in addition to the qauliyah verses, which tends to be taken as explanation of nature and its whole contents. The term environment is closely related to inseparable key words pertaining to the harmony of the environment, namely ecology and ecosystem. The word ecology is derived from Greek words oikos meaning household and logos meaning word science. Therefore, ecology can be defined as the study of the households of living beings. The problem scrutinized in this study is concerning the concept of environmental preservation in the perspective of the Qur'an with a thematic exegesis method. To focus on, sub-problems related to the subject are formulated as follows: First: what is the definition of environment according to the Qur’an and what are the terms applied for that concept? Second: What are the efforts to conserve the environment? Third: How urgent is sustaining the environment to human survival?